The Pythons : Autobiography - Chapman, Graham, 1941-1989 [et al.] (New York Thomas Dunne Books, 2005)
This book includes autobiographies and oral histories of the six members of the Monty Python comedy troupe, as well as stories about the making of the Flying Circus TV series and films. The large coffee table size book contains over 1000 photographs, some never before published and many from the group's private collections. There are also concept sketches, drawings, doodles, and correspondence
Include Color Illustration and Index
Keywords: Monty Python (Comedy troupe) -- Idle, Eric -- Jones, Terry, 1942-